Морські малюнки Дніпрової Чайки в аспекті просодії - Науменко, Наталія Валентинівна (My University, 2025)
У статті показано особливості просодії у наративному стилі Дніпрової Чайки (Людмили Василевської) на основі циклу прозової лірики «Морські малюнки». До уваги взято один із найбільш відомих його складників – твір «Мара», не лише з урахуванням його темпоритмічного та образного ладу, а й як взірець «розповіді про митця», знакового жанроутвору в українській літературі доби модернізму.

The article shows the features of prosody in the narrative style of Dnieper Seagull (Lyudmila Vasilevska) based on the cycle of prose lyrics "Sea Drawings". One of its most famous components, the work "Mara", is taken into account, not only in terms of its tempo-rhythmic and figurative structure, but also as an example of a "story about an artist", a significant genre work in Ukrainian literature of the modernist era.
The author of the article specified about the prosodic elements in the narrative style of Dniprova Chayka (the pen-name of Lyudmyla Vasylevska), having based on the prose lyric cycle ‘Morski malyunky’ (‘The Sea Pictures’). Its most famous constituent, a prose poem ‘Mara’ (A Ghost), was chosen to research, regarding not only the temporhythm and imagery, but also owing to the fact that it was a specimen of ‘a story about an artist,’ which genre modification was quite conceptual for Ukrainian Modernistic literature.
Keywords: українська література; Ukrainian literature; модернізм; modernism; прозова лірика; prose lyrics; просодія; prosody; творчість Дніпрової Чайки; works of Dniproya Chaika; кафедра іноземних мов професійного спрямування